(untitled) (Research, Society and Development, 2022)
The objective of this research was to evaluate the agronomic potential and the nutritional value of forages implanted in consortium with the corn crop. The treatments were distributed in randomized blocks in a 4 x 3 factorial scheme (4 grasses - Urochloa brizantha cv. Marandu, Urochloa brizantha cv. MG4, Urochloa brizantha cv. MG5 and Panicum maximum cv. Mombasa - 3 sowing methods - forage planting together corn sowing, forage planting at the time of corn coverage, coverage and planting of grasses alone), totaling 12 treatments with 4 replications. The following variables were analyzed: tiller number, total dry matter (MST), leaf dry matter (MSF), stem dry matter (MSC), dry matter productivity/ha, percentage of leaves, percentage of stem, neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP) and in vitro dry matter digestibility (DIVMS). The planting method of forages sown without intercropping showed higher numbers of tillers, percentage of leaves, higher productivity, in addition to increasing the in vitro digestibility of DM and reducing the percentage of stems. In view of the results obtained in this research, it was observed that the implantation of forages in consortium with corn, interfered negatively in the establishment of forages in consortium in the grain yield and in the bromatological quality of the forages.